The Mediated Role of Aggressive Behavior in the Relationship Between Self-Esteem and School Refusal Among Adolescents - Maskuri Muhammad Cahyadi; Rita Eka Izzaty (Universitas PGRI Yogyakarta, 2026)
This study began with the emergence of indicators of school refusal behavior, namely truancy among adolescents. Self-esteem and aggressive behavior are factors in the emergence of school refusal. Therefore, this study aims to show the role of aggressive behavior as a mediator between self-esteem and school refusal. This study used a quantitative approach, a cross-sectional survey conducted on 226 students from 14 Junior High Schools in Surakarta. The instruments used were the School Refusal Assessment Scale-Revised (α = 0.752-0.799), the Self-Esteem Inventory scale (α = 0.650-0.722), and the Buss and Perry Aggression Questionnaire scale (α = 0.650-0.720). All scales used have met psychometric requirements and have been validated through Confirmatory Factor Analysis (CFA). Data were analyzed using SEM-PLS software. The results of this study indicate that self-esteem has an indirect effect on school refusal through aggressive behavior, with a significance value of 4.7%. The F-square results for the relationships between self-esteem and school refusal were 0.681 (strong influence), between self-esteem and aggressive behavior 0.125 (moderate influence), and between aggressive behavior and school refusal 0.033 (low influence). The implication of this research is the need for programs by parents and teachers to increase students' self-esteem, thereby reducing aggressive behavior and school refusal. Keywords: aggressive, school refusal, self-esteem